Manufacturing method for high purity SiC crystal

The CVD method using high-temperature conductive heating elements in a reactor effectively addresses the challenges of producing high-purity SiC crystals, achieving high yields and purity suitable for advanced electronic and LED applications.

JP7655888B2Active Publication Date: 2025-04-02OCI CO LTD(KR)
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2022179659
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-11-11
Filing Date
2022-11-09
Publication Date
2025-04-02
Estimated Expiration
2042-11-09

AI Technical Summary

Technical Problem

Conventional methods for producing high-purity silicon carbide (SiC) crystals face challenges in achieving high purity and low impurity content, limiting their use in advanced electronic devices and LED applications.

Method used

A method involving chemical vapor deposition (CVD) using a reactor with conductive heating elements made of high-temperature materials like tungsten or carbon fiber reinforced carbon (CFRC), where silicon and carbon source precursors are mixed with hydrogen and injected into the reaction chamber, allowing for the deposition of high-purity SiC crystals with controlled phase composition.

Benefits of technology

This method enables the mass production of high-purity SiC crystals with a purity of 6N or more and a total content of metal impurities of 1 ppm or less, achieving excellent yields and improved quality and productivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007655888000001
    Figure 0007655888000001
  • Figure 0007655888000002
    Figure 0007655888000002
  • Figure 0007655888000003
    Figure 0007655888000003
Patent Text Reader

Abstract

To provide a method for mass production of high-purity SiC crystals with extremely low impurity content in excellent yields.SOLUTION: A method for producing high-purity SiC crystals of the present invention includes: i) preparing a reactor containing a reaction chamber containing a pair of electrodes connected to a power source and one or more pairs of conductive heating elements electrically connected to the electrodes; ii) heating the conductive heating elements; iii) mixing a silicon source precursor, a carbon source precursor and a carrier gas to prepare a mixed gas; iv) injecting the mixture gas into the reaction chamber; v) depositing SiC on the conductive heating elements; and vi) separating and acquiring the deposited SiC crystals from the conductive heating elements.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing high purity silicon carbide (SiC) crystals, and more particularly to a method for mass-producing high purity SiC with extremely low impurity content at an excellent yield. [Background technology]

[0002] Silicon carbide (SiC) has recently been used as a semiconductor material for a variety of electronic devices and purposes. Silicon carbide is particularly useful because it has high physical strength and resistance to chemical attack. Silicon carbide also has excellent electronic properties, including radiation hardness, a relatively wide band gap, high saturated electron drift velocity, high operating temperature, and absorption and emission of high energy quanta in the blue, violet, and ultraviolet regions of the spectrum.

[0003] Silicon carbide single crystals have the advantage that they can be used at high temperatures instead of Si semiconductors, which have a maximum operating temperature of 250℃, thanks to their high oxidation resistance and excellent electrical properties, and are suitable for manufacturing semiconductor devices that operate in special environments because they are chemically stable and highly resistant to radiation, etc. In addition, in the LED industry, silicon carbide single crystals are used as substrates for growing GaN, which is used in LED substrates, so the demand for high-purity SiC single crystals is increasing as the LED market expands, and this is leading to an increase in the demand for raw materials needed to grow the crystals, as well as the required purity.

[0004] There are various methods for producing high purity silicon carbide powder raw materials in the past, such as the Acheson method, the carbothermal reduction method, and the liquid phase polymer pyrolysis method. In particular, the synthesis method for high purity silicon carbide powder uses the carbothermal reduction method. That is, the carbon source and the silicon source materials are mixed, and the mixture is subjected to a carbonization process and a synthesis process to synthesize silicon carbide powder. However, the conventional methods as described above have a limit in that silicon carbide powders with various crystal phases and purities are produced.

[0005] Korean Patent Publication No. 10-2011-0021530 (Patent Document 1) reports a technology for synthesizing high-purity silicon carbide powder by mixing solid-phase silica and solid-phase carbon raw materials and then subjecting them to a carbothermal reduction reaction at a temperature of 1,600°C to 1,900°C in order to manufacture high-purity granular silicon carbide powder used in manufacturing silicon carbide single crystals by the PVT method.

[0006] U.S. Patent No. 4,702,900 (Patent Document 2) reports a technology for synthesizing high-purity β-phase silicon carbide granular powder by selecting the types of silicon alkoxide and carbon compound to produce a silicon dioxide-carbon precursor, and then heat-treating it under vacuum or in an inert gas such as argon (Ar) to obtain silicon carbide powder.

[0007] In the specification of U.S. Patent Registration No. 5,863,325 (Patent Document 3), the metal impurities in the silicon carbide powder produced by the above process are a few ppm of high-purity β silicon carbide granular powder, and an optimized heat treatment process is disclosed for using the produced β-phase silicon carbide powder as a single crystal raw material.

[0008] As in the specification of U.S. Patent Registration No. 5,704,985 (Patent Document 4), the theoretical SiC density (3.2 g / cm 3Bulk SiC forms approaching 1000 nm in diameter are commercially produced by CVD. In the process, silicon- and carbon-containing gas-phase precursors react at elevated temperatures, typically 1,200°C to 1,400°C, to form solid SiC, which is typically deposited on a suitable substrate such as graphite. A single precursor containing both Si and C atoms, e.g., trimethylsilane, can also be used. Although high purity precursors are available, commercial grade bulk SiC produced by CVD is not sufficiently pure to be used as a crystal source in SiC crystal growth, especially for semi-insulating SiC crystals, as commercial grade bulk SiC typically contains boron (0.7-2 ppm), metallic impurities, and nitrogen (100 ppm or less).

[0009] However, the conventional methods described above have problems in that it is difficult to produce silicon carbide powder economically and that it is not possible to produce it with high purity, so there is still a need to study methods for mass-producing high-purity SiC crystals. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] Korean Patent Publication No. 10-2011-0021530 [Patent Document 2] U.S. Patent No. 4,702,900 [Patent Document 3] U.S. Patent No. 5,863,325 [Patent Document 4] U.S. Patent No. 5,704,985 Summary of the Invention [Problem to be solved by the invention]

[0011] An object of the present invention is to provide a method for solving the limitations of conventional manufacturing methods and for mass-producing high-purity SiC crystals with an extremely low impurity content at an excellent yield.

[0012] The present invention also provides a SiC crystalline body having a single phase having a beta (β) phase or a composite phase in which the α phase and the β phase coexist. [Means for solving the problem]

[0013] The present invention provides a method for producing a high-purity SiC crystal body, comprising the steps of: i) preparing a reactor including a reaction chamber including a pair of electrodes connected to a power source and one or more pairs of conductive heating elements electrically connected to the electrodes; ii) heating the conductive heating elements; iii) mixing a silicon source precursor, a carbon source precursor and a carrier gas to prepare a mixed gas; iv) injecting the mixed gas into the reaction chamber; v) depositing SiC on the conductive heating elements; and vi) separating the deposited SiC crystal body from the conductive heating elements to obtain it.

[0014] In the present invention, the temperature of the conductive heating element can be raised to 1,000°C to 1,800°C, whereby the temperature inside the reaction chamber is heated to 1,000°C to 1,500°C.

[0015] The conductive heating element can be selected from molybdenum (Mo), tungsten (W), platinum (Pt), graphite, carbon fiber reinforced carbon (CFRC), SiC, and polysilicon.

[0016] The conductive heating element may have a form of one or more pairs of filaments.

[0017] The SiC deposition rate on the conductive heating element may be 10 g / hr or more.

[0018] The silicon source precursor may be one or more selected from trichlorosilane (TCS), dichlorosilane (DCS), silicon tetrachloride (STC) and monosilane.

[0019] The silicon source precursor may be trichlorosilane (TCS).

[0020] The carbon source precursor may be propane (C3H8).

[0021] The carrier gas may be hydrogen (H2).

[0022] The Si:C atomic ratio between the silicon source precursor and the carbon source precursor in the mixed gas may be 0.5 to 2:1.

[0023] The Si:C atomic ratio between the silicon source precursor and the carbon source precursor in the mixed gas may be 1:1.

[0024] The present invention provides a SiC crystal mass produced by the above-mentioned method, the SiC crystal mass having a purity of 6N or higher.

[0025] The SiC crystalline body may have a single β phase or a composite phase in which α and β phases coexist.

[0026] The SiC crystal has a total metal impurity content of 1 ppm or less. Effect of the Invention

[0027] The manufacturing method of the present invention is capable of mass-producing high-purity SiC crystals with excellent yield.

[0028] Furthermore, the method of the present invention makes it possible to improve the quality and productivity of SiC crystals.

[0029] Moreover, according to the manufacturing method of the present invention, it is possible to provide the high-purity SiC crystalline body having a total content of metal impurities of 1 ppm or less, and the high-purity SiC crystalline body may have a single β phase or a composite phase in which α phase and β phase coexist. [Brief description of the drawings]

[0030] FIG. 1 is a process flow diagram for producing a high-purity SiC crystalline mass according to an embodiment of the present invention. FIG. 2 is a schematic diagram showing a mass production system for high-purity SiC crystals according to the present invention. FIG. 3 is a schematic diagram of a reactor in the mass production system disclosed in FIG. 4 to 19 are diagrams confirming the peaks of the β and / or α phases in the SiC crystal bodies produced in Examples 1 to 16. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0031] Hereinafter, the embodiments of the present invention will be described in detail with reference to the accompanying drawings so that those skilled in the art can easily carry out the present invention. However, the present invention may be embodied in various different forms and is not limited to the embodiments described herein. In the drawings, parts that are not related to the description are omitted in order to clearly explain the present invention, and the same reference numerals are used throughout the specification to refer to the same or similar components.

[0032] In the description of the embodiments, the description that each layer (film), region, pattern or structure is formed "on" or "under" a substrate, each layer (film), region, pad or pattern includes that each layer (film), region, pad or pattern is formed directly or via another layer. The criteria for "on" or "under" each layer will be described based on the drawings.

[0033] In the drawings, the thickness and size of each layer (film), region, pattern, or structure may be modified for the sake of clarity and convenience of explanation, and therefore may not completely reflect the actual size.

[0034] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings.

[0035] The present invention provides a method for producing high-purity SiC crystalline bodies in large quantities by chemical vapor deposition (CVD).

[0036] A method for producing a high-purity SiC crystal body according to the present invention includes the steps of: i) preparing a reactor including a reaction chamber including a pair of electrodes connected to a power source and one or more pairs of conductive heating elements electrically connected to the electrodes; ii) heating the conductive heating elements; iii) mixing a silicon source precursor, a carbon source precursor, and a carrier gas to prepare a mixed gas; iv) injecting the mixed gas into the reaction chamber; v) depositing SiC on the conductive heating elements; and vi) separating the deposited SiC crystal body from the conductive heating elements (FIG. 1).

[0037] 2 is a schematic diagram of a SiC mass production system according to the present invention. The device configuration not shown in FIG. 2 can be applied to a commonly used chemical vapor deposition (CVD) reactor.

[0038] As shown in the figure, the SiC mass production system according to the present invention is roughly composed of a source material supply section 100 and a reaction section 200.

[0039] The source material supply unit 100 includes a silicon source precursor supply unit 10, a carbon source precursor supply unit 20, a carrier gas supply unit 30, a mixer 40, and a vaporizer 50, and is provided with flowmeters 11, 21, and 31 for adjusting the flow rates of the silicon source precursor supply unit 10, the carbon source precursor supply unit 20, and the carrier gas supply unit 30, respectively. Examples of the flowmeters 11, 21, and 31 that enable selectable fluid communication include MFC, LMFC, and LFC.

[0040] The silicon source precursor supplied to the silicon source precursor supply unit 10 is monosilane or a compound having the general formula SiH n X 4-nHalosilane represented by (n=0, 1, 2, 3; X=Cl, Br, I) is used. Preferably, a chlorinated silane compound can be used. Specifically, trichlorosilane (TCS), dichlorosilane (DCS), silicon tetrachloride (STC) or monosilane can be used, and preferably trichlorosilane (SiHCl3, TCS).

[0041] The carbon source precursor supplied to the carbon source precursor supply 20 may be a hydrocarbon compound such as methane, ethane, propane, etc., and is preferably propane (C3H8).

[0042] The carrier gas supplied to the carrier gas supply unit 30 is preferably hydrogen (H2) or a mixture of hydrogen (H2) and an inert gas (eg, He, Ar, N2), and is preferably hydrogen (H2).

[0043] The pressure inside the silicon source precursor supply part 10, the carbon source precursor supply part 20 and the carrier gas supply part 30 is preferably 2 to 4 bar.

[0044] The mixer 40 uniformly mixes the source materials supplied from the flowmeters 11, 21, and 31, and then flows the mixed gas into the reactor 60 through the vaporizer 50. The mixed gas includes a silicon source precursor, a carbon source precursor, and a carrier gas. The vaporizer 50 allows low volatility materials to be delivered in volume, and induces reproducible delivery and deposition without thermal decomposition of the precursor. The pressure and temperature in the vaporizer 50 can be adjusted, and the pressure in the vaporizer 50 is preferably 0 to 4 bar, and the temperature in the vaporizer 50 is preferably 50°C to 400°C, and more preferably may be in the range of 100°C to 200°C.

[0045] The atomic ratio of Si:C:H in the mixed gas containing the silicon source precursor, the carbon source precursor and the carrier gas flowing into the mixer 40 can be selected according to the contents of these chemical elements and the stoichiometric ratio of these chemical elements.

[0046] In one embodiment of the present invention, the Si:C atomic ratio between the silicon source precursor and the carbon source precursor in the mixed gas may be preferably 0.5 to 2: 1, more preferably 0.75 to 1.5: 1, and even more preferably 1: 1. When the above range is satisfied, the crystallinity and uniformity of the SiC deposited on the conductive heating element are good, and the conversion efficiency of the supplied mixed gas to SiC is high.

[0047] FIG. 3 is a schematic diagram of a reactor in the mass production system disclosed in FIG.

[0048] In one aspect of the present invention, the reactor 60 includes a reaction chamber 600 including a substrate and a reactor cover, at least a pair of electrodes 610 that are installed through the substrate and connected to a power source, and one or more pairs of conductive heating elements 620 that are respectively coupled to the pair of electrodes by electrode chucks and have upper ends connected to each other.

[0049] The reactor 60 forms a reaction chamber 600 on a substrate, and a reactor cover is bonded to the substrate in a gas-tight structure. The reactor 60 includes a bell jar forming the reaction chamber 600 and a chamber cover spaced apart from the bell jar to allow a coolant to flow therebetween.

[0050] One or more pairs of conductive heating elements 620 in the reactor are connected to an external electric energy source 630 via electrodes and electrode terminals at the lower end of the substrate of the reaction chamber 600. Thus, the conductive heating elements 620 form an electric circuit and are heated by passing electricity through the electrodes and electrode terminals.

[0051] The conductive heating element 620 may be one or more pairs of filaments, and such filaments may have any shape. In one embodiment of the present invention, the filaments may be one or more pairs of rod filaments. A pair of rod filaments is formed of a hairpin or U-shaped rod, with two rod filaments standing upright and spaced apart from each other in the reaction chamber, and one horizontal rod filament horizontally connecting the uppermost two ends of the two rod filaments. In addition, the lower ends of the two rod filaments are connected to an external electric energy source via an electrode and an airtight terminal, and one set of rod filaments forms one complete electric circuit.

[0052] Unlike the conventional technology in which the deposition surface on which SiC is deposited in a reactor is indirectly heated, the present invention directly heats the conductive heating element 620 and deposits SiC on the conductive heating element 620. This not only enables fine control of the SiC crystal phase by adjusting the heating temperature of the conductive heating element 620, but also significantly improves the deposition rate of SiC, making it possible to obtain SiC crystals with high purity and high yield.

[0053] The present invention uses a high melting point material or a silicon material as the material for the conductive heating element 620. The high thermal stability of the conductive heating element 620 material of the present invention prevents oxidation, corrosion, cracking, etc. of the deposition surface, and ultimately allows the production of a high-purity SiC crystal.

[0054] In particular, the conductive heating element 620 material has higher strength at high temperatures than metallic materials, and can be used in an inert atmosphere even at ultra-high temperatures of 2000° C. or more, providing high thermal stability.

[0055] The conductive heating element 620 of the present invention may be made of one or more materials selected from the group consisting of molybdenum (Mo), tungsten (W), platinum (Pt), graphite, carbon fiber reinforced carbon (CFRC), SiC, and polysilicon, and is preferably made of tungsten (W) or carbon fiber reinforced carbon (CFRC). More preferably, the conductive heating element 620 is made of carbon fiber reinforced carbon (CFRC), which has excellent thermal properties, dimensional stability, strength, and chemical stability such as corrosion resistance at ultra-high temperatures.

[0056] The carbon fiber reinforced carbon (CFRC) of the present invention includes a carbon fiber reinforced carbon composite (CFRC composite) or a carbon / carbon material (C / C material). The carbon fiber reinforced carbon (CFRC) has physical properties such as light weight, high strength, and high elasticity, as well as high durability and impact resistance. In particular, compared to isotropic graphite materials, the carbon fiber reinforced carbon (CFRC) has high strength, does not bend easily, and does not crack, so that it provides SiC crystals with high purity and high yield even under high temperatures.

[0057] As an example of the carbon fiber reinforced carbon (CFRC), a carbon fiber reinforced carbon composite including a reinforcing matrix can be used, and the composite may include a matrix made of a carbide such as a thermosetting resin or pitch and carbon fibers.

[0058] The conductive heating element 620 is supplied with power from an electric energy supply source 630 and heated to, for example, 1,000°C to 1,800°C, preferably 1,400°C to 1,600°C. When the above range is satisfied, a high yield of SiC crystalline body can be obtained. In addition, the SiC deposition rate on the conductive heating element 620 is improved, and the grown SiC has excellent crystallinity, uniformity, and surface morphology. Ultimately, the method for producing a SiC crystalline body according to the present invention improves the quality and productivity of the SiC crystalline body.

[0059] The temperature inside the reactor increases as the conductive heating element 620 heats up. The temperature inside the reactor can be adjusted, and in one embodiment of the present invention, the reactor is heated to about 1,000°C to 1,500°C.

[0060] The silicon source precursor in the mixed gas flowing into the reactor 60 is thermally decomposed and reacts with the carbon source precursor, so that SiC begins to be deposited on the conductive heating element, and a SiC crystal having a thickness greater than or equal to a certain thickness is produced.

[0061] In one aspect of the invention, the present invention is capable of producing large quantities of SiC crystalline bodies in bulk form from a reaction chamber that includes one or more pairs of electrically conductive heating elements.

[0062] The deposition time of the SiC crystal body can be adjusted for a SiC crystal body having a desired thickness and grain size. The deposition rate can depend on one or more process parameters, including, but not limited to, the deposition temperature, the flow rate of the mixed gas flowing into the reaction chamber through the vaporizer and the temperature of the vaporizer, and / or the pressure of the reactor.

[0063] In one embodiment of the present invention, the deposition rate of SiC is at least 10 g / hr or more, preferably 20 g / hr or more, 30 g / hr or more, 40 g / hr or more, 50 g / hr or more, and particularly preferably 60 g / hr or more.

[0064] The pressure in the reactor can be adjusted as necessary, and in one embodiment of the present invention, may be from 1 bar to 3 bar.

[0065] The SiC crystals obtained in the reactor 60 are crushed / crushed using another device, and the SiC single crystal powder classified according to particle size can be etched / cleaned and then packaged.

[0066] In one embodiment of the present invention, the SiC crystalline body produced by the method described above has a high purity of 6N or more, preferably 7N or more, 8N or more, and particularly preferably 9N or more.

[0067] The SiC crystal has a content of all impurity metal atoms of 1 ppm or less, preferably 0.9 ppm or less, 0.8 ppm or less, 0.7 ppm or less, 0.6 ppm or less, 0.5 ppm or less, 0.4 ppm or less, 0.3 ppm or less, 0.2 ppm or less, more preferably 0.1 ppm or less, which is very low, and particularly preferably 0.05 ppm or less, 0.04 ppm or less, 0.03 ppm or less, 0.02 ppm or less, or 0.01 ppm or less.

[0068] The SiC crystalline body may be a single β phase or a mixed phase of α and β phases, and in the case of a mixed phase, has a nearly stoichiometric composition. In the case of a mixed phase of α and β phases, the majority of the crystal phase may be the β phase.

[0069] When the inside of the reaction chamber is 1000°C to 1500°C, the SiC crystal produced is mostly in the β phase. However, when the temperature of the center of the SiC crystal rises to about 1,800°C or higher during the deposition step, a phase transition occurs in the center, and the SiC crystal is considered to have a mixed phase of α and β phases.

[0070] Meanwhile, the SiC crystal according to the present invention having only or predominantly the β phase has excellent electrical properties and is highly pure at the time of manufacture, and therefore can be used in the electrical materials field, particularly in the semiconductor field, and has high thermal conductivity and excellent heat resistance. EXAMPLES

[0071] The present invention will be described in detail below based on examples, but the present invention is not limited to these examples.

[0072] <Example 1> The experiment was carried out according to the process flow diagram for producing high-purity SiC crystals shown in Figure 1. A conductive heating element made of tungsten (W) was installed in a reactor for chemical vapor deposition and connected to an electrode. The conductive heating element was heated so that the temperature inside the reaction chamber reached about 1050°C (measured with a pyrometer), and TCS (SiHCl3) was used as a silicon source precursor, propane (C3H8) was used as a carbon source precursor, and hydrogen (H2) was used as a carrier gas, which were mixed in a mixer, vaporized, and injected into the reaction chamber. At this time, the atomic ratio of Si:C:H in the TCS, propane, and hydrogen present in the mixed gas was set to 0.75:1:5, and the mixed gas was injected at a rate of 10 SLM, and the deposition process was carried out with a deposition rate of SiC of 25.37g / hr.

[0073] The SiC crystal deposited on the conductive heating element was separated to obtain the SiC with a density of 3.18 g / cm. 3 In order to analyze the physical properties of the obtained SiC, an X-ray diffraction analysis was carried out, and as a result, it was confirmed that the peak of the β phase was the largest, as shown in Figure 4.

[0074] <Example 2> A conductive heating element made of tungsten (W) was installed in a reactor for chemical vapor deposition and connected to an electrode. The conductive heating element was heated so that the temperature inside the reaction chamber reached about 1050°C (measured by a pyrometer), and TCS (SiHCl3) was used as a silicon source precursor, propane (C3H8) was used as a carbon source precursor, and hydrogen (H2) was used as a carrier gas, which were mixed in a mixer, vaporized, and injected into the reaction chamber. At this time, the atomic ratio of Si:C:H in the TCS, propane, and hydrogen present in the mixed gas was set to 0.75:1:5, and the mixed gas was injected at a rate of 10 SLM, and the deposition process was carried out with a deposition rate of SiC of 24.20g / hr.

[0075] The SiC crystal deposited on the conductive heating element was separated to obtain the SiC with a density of 3.16 g / cm.3 In order to analyze the physical properties of the obtained SiC, an X-ray diffraction analysis was carried out, and as a result, it was confirmed that the peak of the β phase was the largest, as shown in Figure 5.

[0076] <Example 3> A conductive heating element made of graphite was installed in a reactor for chemical vapor deposition and connected to an electrode. The conductive heating element was heated so that the temperature inside the reaction chamber reached about 1050°C (measured by a pyrometer), and TCS (SiHCl3) was used as a silicon source precursor, propane (C3H8) was used as a carbon source precursor, and hydrogen (H2) was used as a carrier gas, which were mixed in a mixer, vaporized, and injected into the reaction chamber. At this time, the atomic ratio of Si:C:H in the TCS, propane, and hydrogen present in the mixed gas was 0.75:1:5, and the mixed gas was injected at a rate of 10 SLM, and the deposition process was carried out with a deposition rate of SiC of 11.05g / hr.

[0077] The SiC crystal deposited on the conductive heating element was separated to obtain the SiC with a density of 3.22 g / cm. 3 In order to analyze the physical properties of the obtained SiC, an X-ray diffraction analysis was carried out, and as a result, it was confirmed that the peak of the β phase was the largest, as shown in Figure 6.

[0078] <Example 4> A conductive heating element made of graphite was installed in a reactor for chemical vapor deposition and connected to an electrode. The conductive heating element was heated so that the temperature inside the reaction chamber reached about 1150°C (measured by a pyrometer), and TCS (SiHCl3) was used as a silicon source precursor, propane (C3H8) was used as a carbon source precursor, and hydrogen (H2) was used as a carrier gas, which were mixed in a mixer, vaporized, and injected into the reaction chamber. At this time, the atomic ratio of Si:C:H in the TCS, propane, and hydrogen present in the mixed gas was 0.75:1:5.5, and the mixed gas was injected at a rate of 10 SLM, and the deposition process was carried out with a deposition rate of SiC of 47.69g / hr.

[0079] The SiC crystal deposited on the conductive heating element was separated to obtain the SiC with a density of 3.16 g / cm. 3 In order to analyze the physical properties of the obtained SiC, an X-ray diffraction analysis was carried out, and as a result, it was confirmed that the peak of the β phase was the largest, as shown in Figure 7.

[0080] <Example 5> A conductive heating element made of silicon was installed in a reactor for chemical vapor deposition and connected to an electrode. The conductive heating element was heated so that the temperature inside the reaction chamber reached about 1050°C (measured by pyrometer), and TCS (SiHCl3) was used as a silicon source precursor, propane (C3H8) was used as a carbon source precursor, and hydrogen (H2) was used as a carrier gas, which were mixed in a mixer, vaporized, and injected into the reaction chamber. At this time, the atomic ratio of Si:C:H in the TCS, propane, and hydrogen present in the mixed gas was 0.75:1:5.5, and the mixed gas was injected at a rate of 10 SLM, and the deposition process was carried out with a deposition rate of SiC of 24.32g / hr.

[0081] The SiC crystal deposited on the conductive heating element was separated to obtain the SiC with a density of 3.18 g / cm. 3 In order to analyze the physical properties of the obtained SiC, an X-ray diffraction analysis was carried out, and as a result, it was confirmed that the peak of the β phase was the largest, as shown in Figure 8.

[0082] <Example 6> A conductive heating element made of silicon was installed in a reactor for chemical vapor deposition and connected to an electrode. The conductive heating element was heated so that the temperature inside the reaction chamber reached about 1100°C (measured by pyrometer), and TCS (SiHCl3) was used as a silicon source precursor, propane (C3H8) was used as a carbon source precursor, and hydrogen (H2) was used as a carrier gas, which were mixed in a mixer, vaporized, and injected into the reaction chamber. At this time, the atomic ratio of Si:C:H in the TCS, propane, and hydrogen present in the mixed gas was 0.75:1:5.5, and the mixed gas was injected at a rate of 10 SLM, and the deposition process was carried out with a deposition rate of SiC of 26.53g / hr.

[0083] The SiC crystal deposited on the conductive heating element was separated to obtain the SiC with a density of 3.22 g / cm. 3 In order to analyze the physical properties of the obtained SiC, an X-ray diffraction analysis was carried out, and as a result, it was confirmed that the peak of the β phase was the largest, as shown in FIG.

[0084] <Example 7> A conductive heating element made of silicon was installed in a reactor for chemical vapor deposition and connected to an electrode. The conductive heating element was heated so that the temperature inside the reaction chamber reached about 1170°C (measured by pyrometer), and TCS (SiHCl3) was used as a silicon source precursor, propane (C3H8) was used as a carbon source precursor, and hydrogen (H2) was used as a carrier gas, which were mixed in a mixer, vaporized, and injected into the reaction chamber. At this time, the atomic ratio of Si:C:H in the TCS, propane, and hydrogen present in the mixed gas was 0.75:1:5.5, and the mixed gas was injected at a rate of 10 SLM, and the deposition process was carried out with a deposition rate of SiC of 32.07g / hr.

[0085] The SiC crystal deposited on the conductive heating element was separated to obtain the SiC with a density of 3.19 g / cm. 3In order to analyze the physical properties of the obtained SiC, an X-ray diffraction analysis was carried out, and as a result, it was confirmed that the peak of the β phase was the largest, as shown in FIG.

[0086] <Example 8> A conductive heating element made of silicon was installed in a reactor for chemical vapor deposition and connected to an electrode. The conductive heating element was heated so that the temperature inside the reaction chamber reached about 1050°C (measured by a pyrometer), and TCS (SiHCl3) was used as a silicon source precursor, propane (C3H8) was used as a carbon source precursor, and hydrogen (H2) was used as a carrier gas, which were mixed in a mixer, vaporized, and injected into the reaction chamber. At this time, the atomic ratio of Si:C:H in the TCS, propane, and hydrogen present in the mixed gas was set to 0.75:1:5, and the mixed gas was injected at a rate of 10 SLM, and the deposition process was carried out with a deposition rate of SiC of 25.05g / hr.

[0087] The SiC crystal deposited on the conductive heating element was separated to obtain the SiC with a density of 3.15 g / cm. 3 In order to analyze the physical properties of the obtained SiC, an X-ray diffraction analysis was carried out, and as a result, it was confirmed that the peak of the β phase was the largest, as shown in FIG.

[0088] <Example 9> A conductive heating element made of carbon fiber reinforced carbon (CFRC) was installed in a reactor for chemical vapor deposition and connected to an electrode. The conductive heating element was heated so that the temperature inside the reaction chamber reached about 1050℃ (measured by pyrometer), and TCS (SiHCl3) was used as a silicon source precursor, propane (C3H8) was used as a carbon source precursor, and hydrogen (H2) was used as a carrier gas, which were mixed in a mixer, vaporized, and injected into the reaction chamber. At this time, the atomic ratio of Si:C:H in the TCS, propane, and hydrogen present in the mixed gas was 0.75:1:5.5, and the mixed gas was injected at a rate of 10 SLM, and the deposition process was carried out with a deposition rate of SiC of 30.58g / hr.

[0089] The SiC crystal deposited on the conductive heating element was separated to obtain the SiC with a density of 3.18 g / cm. 3 In order to analyze the physical properties of the obtained SiC, an X-ray diffraction analysis was carried out, and as a result, it was confirmed that the peak of the β phase was the largest, as shown in FIG.

[0090] <Example 10> A conductive heating element made of carbon fiber reinforced carbon (CFRC) was installed in a reactor for chemical vapor deposition and connected to an electrode. The conductive heating element was heated so that the temperature inside the reaction chamber reached about 1170°C (measured by pyrometer), and TCS (SiHCl3) was used as a silicon source precursor, propane (C3H8) was used as a carbon source precursor, and hydrogen (H2) was used as a carrier gas, which were mixed in a mixer, vaporized, and injected into the reaction chamber. At this time, the atomic ratio of Si:C:H in the TCS, propane, and hydrogen present in the mixed gas was 0.75:1:5.5, and the mixed gas was injected at a rate of 10 SLM, and the deposition process was carried out with a deposition rate of SiC of 39.66g / hr.

[0091] The SiC crystal deposited on the conductive heating element was separated to obtain the SiC having a density of 3.20 g / cm. 3In order to analyze the physical properties of the obtained SiC, an X-ray diffraction analysis was carried out, and as a result, it was confirmed that the peak of the β phase was the largest, as shown in FIG.

[0092] <Example 11> A conductive heating element made of carbon fiber reinforced carbon (CFRC) was installed in a reactor for chemical vapor deposition and connected to an electrode. The conductive heating element was heated so that the temperature inside the reaction chamber reached about 1150°C (measured by pyrometer), and TCS (SiHCl3) was used as a silicon source precursor, propane (C3H8) was used as a carbon source precursor, and hydrogen (H2) was used as a carrier gas, which were mixed in a mixer, vaporized, and injected into the reaction chamber. At this time, the atomic ratio of Si:C:H in the TCS, propane, and hydrogen present in the mixed gas was 0.75:1:5.5, and the mixed gas was injected at a rate of 10 SLM, and the deposition process was carried out with a deposition rate of SiC of 30.94g / hr.

[0093] The SiC crystal deposited on the conductive heating element was separated to obtain the SiC with a density of 3.16 g / cm. 3 In order to analyze the physical properties of the obtained SiC, an X-ray diffraction analysis was carried out, and as a result, it was confirmed that the peaks of α and β phases existed together, as shown in FIG.

[0094] <Example 12> The experiment was carried out according to the process flow diagram for producing high-purity SiC crystals shown in Figure 1. A conductive heating element made of CFRC (Carbon Fiber Reinforced Carbon) was installed in a reactor for chemical vapor deposition and connected to an electrode. The conductive heating element was heated so that the temperature inside the reaction chamber was about 1500℃ or more (measured with a pyrometer), and TCS (SiHCl3) was used as the silicon source precursor, propane (C3H8) was used as the carbon source precursor, and hydrogen (H2) was used as the carrier gas, which were mixed in a mixer, vaporized, and injected into the reaction chamber. At this time, the atomic ratio of Si:C:H in the TCS, propane, and hydrogen present in the mixed gas was 1.5:1:5.5, and the mixed gas was injected at a rate of 5 SLM, and the deposition process was carried out with a deposition rate of SiC of 49.4g / hr.

[0095] The SiC crystal deposited on the conductive heating element was separated to obtain the SiC with a density of 3.15 g / cm. 3 In order to analyze the physical properties of the obtained SiC, an X-ray diffraction analysis was carried out, and as a result, it was confirmed that the peak of the β phase was the largest, as shown in FIG.

[0096] <Example 13> The experiment was carried out according to the process flow diagram for producing high-purity SiC crystals shown in Figure 1. A conductive heating element made of CFRC was installed in a reactor for chemical vapor deposition and connected to an electrode. The conductive heating element was heated so that the temperature inside the reaction chamber reached 1500°C or higher (measured with a pyrometer), and TCS (SiHCl3) was used as the silicon source precursor, propane (C3H8) was used as the carbon source precursor, and hydrogen (H2) was used as the carrier gas, which were mixed in a mixer, vaporized, and injected into the reaction chamber. At this time, the atomic ratio of Si:C:H in the TCS, propane, and hydrogen present in the mixed gas was set to 1:1:5.5, and the mixed gas was injected at a rate of 5 SLM, and the deposition process was carried out with a deposition rate of SiC of 40.9g / hr.

[0097] The SiC crystal deposited on the conductive heating element was separated to obtain the SiC with a density of 3.18 g / cm. 3 In order to analyze the physical properties of the obtained SiC, an X-ray diffraction analysis was carried out, and as a result, it was confirmed that the peak of the β phase was the largest, as shown in FIG.

[0098] <Example 14> The experiment was carried out according to the process flow diagram for producing high-purity SiC crystals shown in Figure 1. A conductive heating element made of CFRC was installed in a reactor for chemical vapor deposition and connected to an electrode. The conductive heating element was heated so that the temperature inside the reaction chamber was about 1500°C or more (measured with a pyrometer), and TCS (SiHCl3) was used as the silicon source precursor, propane (C3H8) was used as the carbon source precursor, and hydrogen (H2) was used as the carrier gas, which were mixed in a mixer, vaporized, and injected into the reaction chamber. At this time, the atomic ratio of Si:C:H in the TCS, propane, and hydrogen present in the mixed gas was 1:1:5.5, and the mixed gas was injected at a rate of 5 SLM, and the deposition process was carried out with a deposition rate of SiC of 41.6g / hr.

[0099] The SiC crystal deposited on the conductive heating element was separated to obtain the SiC with a density of 3.19 g / cm. 3 In order to analyze the physical properties of the obtained SiC, an X-ray diffraction analysis was carried out, and as a result, it was confirmed that the peak of the β phase was the largest, as shown in FIG.

[0100] <Example 15> The experiment was carried out according to the process flow diagram for producing high-purity SiC crystals shown in Figure 1. A conductive heating element made of CFRC was installed in a reactor for chemical vapor deposition and connected to an electrode. The conductive heating element was heated so that the temperature inside the reaction chamber was about 1500°C or more (measured with a pyrometer), and TCS (SiHCl3) was used as the silicon source precursor, propane (C3H8) was used as the carbon source precursor, and hydrogen (H2) was used as the carrier gas, which were mixed in a mixer, vaporized, and injected into the reaction chamber. At this time, the atomic ratio of Si:C:H in the TCS, propane, and hydrogen present in the mixed gas was 1:1:5.5, and the mixed gas was injected at a rate of 5 SLM, and the deposition process was carried out with a deposition rate of SiC of 40.6g / hr.

[0101] The SiC crystal deposited on the conductive heating element was separated to obtain the SiC with a density of 3.17 g / cm. 3 In order to analyze the physical properties of the obtained SiC, an X-ray diffraction analysis was carried out, and as a result, it was confirmed that the peak of the β phase was the largest, as shown in FIG.

[0102] <Example 16> The experiment was carried out according to the process flow diagram for producing high-purity SiC crystals shown in Figure 1. A conductive heating element made of CFRC was installed in a reactor for chemical vapor deposition and connected to an electrode. The conductive heating element was heated so that the temperature inside the reaction chamber was about 1500°C or more (measured with a pyrometer), and TCS (SiHCl3) was used as the silicon source precursor, propane (C3H8) was used as the carbon source precursor, and hydrogen (H2) was used as the carrier gas, which were mixed in a mixer, vaporized, and injected into the reaction chamber. At this time, the atomic ratio of Si:C:H in the TCS, propane, and hydrogen present in the mixed gas was 1:1:5.5, and the mixed gas was injected at a rate of 5 SLM, and the deposition process was carried out with a deposition rate of SiC of 41.5g / hr.

[0103] The SiC crystal deposited on the conductive heating element was separated to obtain the SiC with a density of 3.17 g / cm. 3 In order to analyze the physical properties of the obtained SiC, an X-ray diffraction analysis was carried out, and as a result, it was confirmed that the peak of the β phase was the largest, as shown in FIG. [Explanation of symbols]

[0104] 100 Raw material supply department 200 Reaction unit 10. Silicon source precursor supply section 20 Carbon source precursor supply section 30 Carrier gas supply unit 40 mixer 50 Carburetor 60 Reactor 11, 21, 31 Flowmeter 600 Reaction Chamber 610 Pair of electrodes 620 Conductive Heating Element 630 Electrical Energy Supply Source

Claims

1. 1. A method for producing a high-purity SiC crystalline body, comprising the steps of: i) preparing a reactor including a reaction chamber including a pair of electrodes connected to a power source and one or more pairs of conductive heating elements electrically connected to the electrodes, wherein the conductive heating elements are made of carbon fiber reinforced carbon (CFRC); ii) directly heating the electrically conductive heating element; iii) mixing a silicon source precursor, a carbon source precursor and a carrier gas; iv) injecting the gas mixture into the reaction chamber; v) depositing SiC on the conductive heating element; vi) obtaining the deposited SiC crystal by separating it from the conductive heating element; the Si:C atomic ratio between the silicon source precursor and the carbon source precursor is 0.75 to 1.5:1; A method for producing a SiC crystal.

2. The method of claim 1 , wherein the electrically conductive heating element has a configuration of one or more pairs of filaments.

3. 10. The method of claim 1, wherein the SiC deposition rate on the conductive heating element is 10 g / hr or greater.

4. 2. The method of claim 1, wherein the silicon source precursor is one or more selected from trichlorosilane (TCS), dichlorosilane (DCS), silicon tetrachloride (STC) and monosilane.

5. 10. The method of claim 1, wherein the silicon source precursor is trichlorosilane (TCS).

6. The carbon source precursor is propane (C 3 H 8 2. The method of claim 1 , wherein

7. The carrier gas is hydrogen (H 2 2. The method of claim 1 , wherein

8. 2. The method of claim 1, wherein the atomic ratio of Si:C between the silicon source precursor and the carbon source precursor in the gas mixture is 1:1.

Citation Information

Patent Citations

  • Improvements in or relating to the production of ultra-pure silicon carbide

    GB1029473A

  • Production of article having silicon carbide film

    JP1986295372A

  • Production of polycrystalline silicon

    JP1988123806A

  • Member for heat treatment of high-purity CVD-sic semiconductor and its manufacture

    JP1998012563A

  • System for growing silicon carbide crystals

    JP2006527157A